الأساس القانوني لعقد القرض العام - حنون، عذراء كاطع (جامعة واسط - كلية الآداب, 2016)
Public Loan is a an amount of money received by the state or its agencies from the individuals, in return, the state gave back the principal plus the interests rate agreed upon between them. Scholars have not agree about the legal nature of the public loan, Some regarded it as an administrative contract while other consider it as a type of sovereign acts which enable the state to amend it according to her needs. Other approach stipulate that Public Loan should be cancelled only by law because issue Public Loan come only by law. Most Constitutions make Public Loan part of exclusive authority to legislature, no Public Loan can be issued without its approval.
يعرف عقد القرض العام على أنه مبلغ من المال تحصل عليه الدولة أو إحدى هيئاتها العامة من الأخرين على أن تتعهد الدولة برده مع فوائده وفق الآجال المتفق عليها. أما من حيث طبيعته القانونية فقد اختلف الفقهاء فيما بينهم فبعضهم عده من عقود القانون العام الإداري، والبعض عده عمل من أعمال السيادة فيحق للدولة أن تغيره على وفق ما تراه ملائم لظروفها، أما الرأي الأخر فيرى أن عقد القرض لا يصدر إلا بقانون فانه لا يلغى إلا بقانون أخر، ولأهمية عقد القرض اشترطت أغلب دساتير الدول أن يكون انعقاد عقد القرض من الاختصاص الحصري للسلطة التشريعية فلا يعقد عقد القرض دون موافقة السلطة التشريعية.
Keywords: القروض العامة -- العقود المالية -- القانون المالي